Mind and Matter Challenges and Opportunities in Cognitive Semiotics and Aesthetics - López-Varela Azcárate, Asun (IntechOpen, 2022)
Do brains create material reality in thinking processes or is it the other way around, with things shaping the mind? Where is the location of meaning-making? How do neural networks become established by means of multimodal pattern replications, and how are they involved in conceptualization? How are resonance textures within cellular entities extended in the body and the mind by means of mirroring processes? In which ways do they correlate to consciousness and self-consciousness? Is it possible to explain out-of-awareness unconscious processes? What holds together the relationship between experiential reality, bodily processes like memory, reason, or imagination, and sign-systems and simulation structures like metaphor and metonymy visible in human language? This volume attempts to answer some of these questions.